DECENTRALIZATION DYNAMICS: ASSESSING LOCAL GOVERNMENT PERFORMANCE IN LINGGA - Mulyani, Sri; Kurniawan, E.Dody; hariono, Desrian; Yosrizal, Yosrizal; Zurrahman, Zurrahman; marlissawaty, Fikky (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2024)
This study examines the implementation of decentralization in Lingga, Indonesia, focusing on the performance of the local government (Pemda) and its impacts on community engagement and public service delivery. Utilizing a qualitative case study approach, the research reveals both significant successes and ongoing challenges associated with decentralization. While increased local autonomy has fostered greater community participation and responsiveness to local needs, persistent issues such as financial dependency, bureaucratic inefficiencies, and geographic isolation hinder effective governance. The findings highlight disparities in public service access, particularly for marginalized communities in remote areas. The study contributes to the broader discourse on decentralization by emphasizing the need for context-specific policies that address local realities. Based on these insights, several policy recommendations are proposed, including enhanced financial support for local governments, capacity-building initiatives for local officials, and the development of inclusive governance mechanisms. These measures aim to strengthen the implementation of decentralization in Lingga, ensuring that it delivers equitable and effective governance outcomes for all residents.